Step responses of a torsional system with multiple clearances: Study of vibro-impact phenomenon using experimental and computational methods. (15th January 2018) - Oruganti, Pradeep Sharma; Krak, Michael D.; Singh, Rajendra
Graphical abstract: Highlights: Step responses of a 3DOF torsional system with one, two or three clearances examined. New measurements acquired on a scientific experiment with controlled clearances. Minimal order, non-linear torsional models are experimentally validated. Softening nonlinearity trends observed in time-varying periods of oscillations. Six impulsive metrics evaluated and correlated with measured accelerations. Abstract: Recently Krak and Singh (2017) proposed a scientific experiment that examined vibro-impacts in a torsional system under a step down excitation and provided preliminary measurements and limited non-linear model studies. A major goal of this article is to extend the prior work with a focus on the examination of vibro-impact phenomena observed under step responses in a torsional system with one, two or three controlled clearances. First, new measurements are made at several locations with a higher sampling frequency. Measured angular accelerations are examined in both time and time-frequency domains. Minimal order non-linear models of the experiment are successfully constructed, using piecewise linear stiffness and Coulomb friction elements; eight cases of the generic system are examined though only three are experimentally studied. Measured and predicted responses for single and dual clearance configurations exhibit double sided impacts and time varying periods suggest softening trends under the step down torque. Non-linear models are experimentally validated by comparing results with new measurements and with those previously reported. Several metrics are utilized to quantify and compare the measured and predicted responses (including peak to peak accelerations). Eigensolutions and step responses of the corresponding linearized models are utilized to better understand the nature of the non-linear dynamic system. Finally, the effect of step amplitude on the non-linear responses is examined for several configurations, and hardening trends are observed in the torsional system with three clearances.